Ecological and Digital Transition in Cities: Measuring Ecosystem Services for Urban Planning and Design (Lecture Notes in Networks and Systems, 2025)
This open access book delves into the intersection of ecological, technological, and social dynamics at the core of urban transition and the relevance of urban planning and design in addressing the pressing challenges faced by cities and regions in the 21st century. This book is held at “Networks, Markets & People” Communities, Institutions and Enterprises toward post-humanism epistemologies and AI challenges, May 22–25, 2024, Reggio Calabria, Italy. The papers included in the book follow two main drivers. The first is dedicated to discussing the concept of ecosystem services exploring the role of policy and governance mechanisms in promoting the integration of ecosystem services into urban planning and design practices. The second presents various data-driven perspectives, methodologies, frameworks, and case studies for measuring ecosystem services in cities, ranging from traditional methods to cutting-edge digital mapping and modeling techniques. The book primarily targets academics, researchers, and students (undergraduate, postgraduates, Ph.D. students) providing interesting insights on the topic that can be useful for urban planning and design course in the urban studies, architecture, and engineering fields. It targets also policymakers, experts, professionals, and consultants active in the urban planning and design field involved in managing the transition of regions and cities